WAQF AS A SUSTAINABLE POVERTY-ALLEVATION MECHANISM IN AFRICA - Adamu, Adamu Abubakar Muhammad; Kolo Malum Barde; Rabi Shehu Dalhatu; Ibrahim Abubakar Muhammad (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2026)
Waqf, a perpetual charity endowment with strong roots in Islamic socioeconomic theory, has resurfaced as a practical and multifaceted approach to tackling the enduring and intricate reality of poverty throughout Africa. Waqf institutions have a long history on the continent, but their developmental potential is still largely untapped because of shoddy legislative frameworks, disjointed administration systems, and low public awareness. This study investigates waqf's potential to serve as a comprehensive strategy for reducing poverty that can produce long-term, sustainable social benefit. The study employed a qualitative research design backed by doctrinal analysis, historical review, and thematic assessment of modern waqf practices. The findings demonstrate how reviving waqf institutions in Africa through contemporary financial models like cash waqf, corporate waqf, and digital waqf platforms can increase funding for necessary services while empowering underprivileged populations through micro-enterprise financing, skill development, and entrepreneurship support. Furthermore, the study contends that waqf's focus on distributive justice and social solidarity is consistent with modern development frameworks, such as the Sustainable Development Goals (SDGs), especially those pertaining to poverty alleviation, decent labour, high-quality education, and decreased inequality. It concludes that, waqf offers a morally good and community-driven framework that can restore dignity, resilience, and inclusive progress throughout African countries in addition to an economically sound method of reducing poverty.